Seven new species of Canthochilum Chapin from Hispaniola (Coleoptera: Scarabaeidae: Scarabaeinae) - Philips, T. Keith; Ivie, Michael A. (Zootaxa, 2008)
Seven new species, Canthochilum brodzinskyorum NEW SPECIES, Canthochilum magnum NEW SPECIES, Canthochilum matthewsi NEW SPECIES, Canthochilum mimicum NEW SPECIES, Canthochilum nebulonemi NEW SPECIES, Canthochilum platycnemis NEW SPECIES, and Canthochilum xericum NEW SPECIES, are described from Hispaniola. New distribution records are given for C. cibony Matthews and C. darlingtoni Matthews in the Dominican Republic.